Successive phase transitions in single-crystalline (C2H5NH3)2CuCl4 and potential of multiferroicity. (March 2019) - Sakami, Tatsuhiro; Ohtani, Toshihiro; Matsumoto, Yasuhiro; Ochi, Daito; Xi, Xiaojuan; Kamikawa, Shuhei; Ohyama, Junpei; Ishii, Isao; Suzuki, Takashi
Abstract: Various experiments, such as X-ray diffraction, polarization microscopy, relative permittivity, spontaneous electric polarization and ferroelectric loop measurements, have been performed on single crystals of a perovskite-type layered compound ( C 2 H 5 N H 3 ) 2 C u C l 4 . The crystal structure of this compound at 273 K and 100 K is determined as Abma and Pbca, respectively. In the polarization microscopy experiments, disappearance of the ferroelastic domain under a stress has been found at 370 K, suggesting that the crystal structure above 370 K is tetragonal ( I 4∕ mmm ). We have found, for the first time, a remarkable anomaly at T C = 25.8 K in the temperature dependence of the relative permittivity. In D-E hysteresis measurements, the ferroelectric loop opens below T C, where D is the electric displacement field and E is the electric field, respectively. The remnant polarization reaches 8 μC/m 2 at 5 K. These results indicate that there is a weak ferroelectric ordering at T C . The clear D-E hysteresis curve is detected below T N = 10 K, which is a weak ferromagnetic transition temperature, suggesting that the weak ferroelectric and the weak ferromagnetic states coexist below T N . Highlights: Crystal structures of (C2 H5 NH3 )2 CuCl4 at 273 K and 100 K are Abma and Pbca, respectively. Structural domain at 360 K is observed by polarizing microscope observation, it disappears at 370 K. A remarkable anomaly in relative permittivity is observed at T C = 25.8 K. Remnant polarization reaches 8 μC/m 2 at 5 K. Ferroelectric hysteresis loop emerges below T C in electric field dependence of electric polarization.